Du concept d’« innovation sociale » - Prades, Jacques (Revue internationale de l'économie sociale : recma, 2015)
Un article de la revue Revue internationale de l'économie sociale, diffusée par la plateforme Érudit.
Publisher: Association Recma
Keywords: Coopératives; Définition; Europe; Histoire; Innovation technologique; Économie

Analyzing Citizen Participation and Engagement in European Smart Cities - Cortés-Cediel, María E.; Iván, Cantador; Rodríguez, Bolívar Manuel Pedro (Social Science Computer Review, 2021)
With the advent of smart cities (SCs), governance has been placed at the core of the debate on how to create public value and achieve a high quality of life in urban environments. In particular, given that public value is rooted in democratic theory and new technologies that promote networking spaces have emerged, citizen participation represents one of the principal instruments to make government open and close to the citizenry needs. Participation in urban governance has undergone a great development: from the first postmodernist ideals of countering expert dominance to today’s focus on learning and social innovation, where citizen participation is conceptualized as co-creation and co-production. Despite this development, there is a lack of research to know how this new governance context is taking place in the SC arena. Addressing this situation, in this article, we present an exhaustive survey of the research literature and a deep study of the experience in participative initiatives followed by SCs in Europe. Through an analysis of 149 SC initiatives from 76 European cities, we provide interesting insights about how participatory models have been introduced in the different areas and dimensions of the cities, how citizen engagement is promoted in SC initiatives, and whether the so-called creative SCs are those with a higher number of projects governed in a participatory way.
Number: 4 Num Pages: 592-626 Place: Thousand Oaks, United States Publisher: SAGE PUBLICATIONS, INC.
Keywords: Co-création; Co-production; Europe; Modèle participatif; Nouvelles technologies; Projets participatifs; Réservé UdeM; Urbanisme; Villes intelligentes

Co-creating social innovation in quadruple helixes: evidence from Sweden - Öberg, Åsa; Albats, Ekaterina; Stefan, Ioana; Johansson, Peter E. (Proceedings of ISPIM Conferences, 2021)
In an increasingly globalized world, the challenges of society need to be tackled not by single organisations but by a multitude of stakeholders. Universities can contribute by extending their role and by collaborating with external stakeholders. This study employs qualitative methods to explore how a university engages with its innovation ecosystem through two different projects.The findings, connected to the development of educational and digital systems,show: 1) evidence of two extreme approaches to external stakeholder engagement and 2) three levels of tensions (multi-layered tensions) - on an overarching level, between stakeholder groups, and within groups of stakeholders. The contribution connects to literature on open innovation, quadruple helixes and lastly to university social innovation, especially responsibility diffusion.
N'AVONS PAS ACCÈS
Keywords: Co-création; Europe; Quadruple helix approach

Framing improvements of public innovation in a living lab context: Processual learning, restrained space and democratic engagement - Fuglsang, Lars; Hansen, Anne Vorre (Research Policy, 2022)
Public innovation has received increasing attention in recent years. Experiments with new governance structures, such as New Public Management and New Public Governance, have challenged the traditional top-down, internally driven forms of innovation in the public sector and have entailed a search for new forms of open, collaborative and interactive innovation, implying a reframing of public innovation activities. However, introducing these new frames of innovation causes uncertainties in the public sector, necessitating better understanding of how public innovation can be changed to address societal needs. This paper uses materials from case studies of 21 public living labs across Europe to analyse the lessons that can be learned from public sector participation in living labs in terms of their contribution to reframing public innovation. The “frame” construct is used to analyse and provide an understanding of how participation in living labs helps public actors to reframe innovation and address public and societal needs. Three living lab framings for changing public innovation are identified (processual learning, restrained space and democratic engagement), and the degree of intensity of these framings with respect to involving stakeholders and addressing societal challenges is discussed. The paper contributes to knowledge of public sector innovation by extending previous accounts of how public innovation can be improved.
Number: 1
Keywords: Europe; Innovation publique; Laboratoire vivant; Libre accès; Living Labs

Integrating Co-Creation, Design Thinking and Responsibility – tools and methods for participatory innovation processes (working title) - Vogel-Pöschl, Heike; Kuhn, Rainer; Maisch, Bettina; Schönherr, Norma; Martinuzzi, André (Proceedings of ISPIM Conferences, 2019)
Responsible Innovation can be the corporate answer to tackle the grand societal challenges. However, companies still have not implemented the concept in their daily innovation practices. Furthermore, citizens, as the voice of societal needs and issues, only have been involved in corporate innovation processes (design thinking, co-creation) on a very limited scale. This raises the question on how to enable the participation of citizens in corporate innovation processes in an effective and efficient way. Therefore, certain quality criteria need to be defined and tested, which has not been researched before in such a context. The aim of this exploratory case study, thus, is to develop and test quality criteria of citizen participation and find out what quality companies can reach in 20 pilot-workshops all over Europe.
N'AVONS PAS ACCÈS
Keywords: Co-création; Europe; Participation; Participation citoyenne

First domino tile in the social innovation process: Idea creation of university students - Yıldırım, Nihan; Ansal, Hacer (2016 Portland International Conference on Management of Engineering and Technology (PICMET), 2016)
Interrelations between creativity, innovativeness and entrepreneurial skills of individuals have long been discussed in the literature. Due to the challenges regarding their measurement, most studies focused on the intentions rather than the outcomes. The idea generation that requires creativity is the first stage of social innovation. The young population's creative potentials in participating social innovation practices deserve a special attention as they play a critical role in the innovativeness and entrepreneurship of societies. This study aims to explore the factors that determine the creative intentions of university students that are important in generating social innovation projects. A structured survey based on the literature was conducted among 600 management and engineering students from 3 universities from the different percentiles of the Entrepreneurial and Innovative University Index for 2012 of the Turkish Ministry of Science, Industry and Technology. The survey included questions on the demographic characteristics, environmental factors, motivators, university/institutional context, perceptions and creative thinking attitudes. By conducting reliability and factor analysis, accuracy and validity of data is tested and the impact factors were identified. Findings reveal that visionary attitude, curiosity, exploration and learning, attitude for own creativity, self-esteem, perception about the learnability of creativity, university and social environment are components of creative thinking intentions of students and some of these factors vary by year of study and university.
Keywords: Entrepreneuriat; Europe; Innovation sociale; Réservé UdeM; Rôle des universités; Université

Social innovation in high-quality agricultural systems: metrics for assessing processes and outcomes - Santini Pigatto, Giuliana Aparecida; Brunori, Gianluca (Innovation: The European Journal of Social Science Research, 2021)
Social innovation and high-quality agricultural systems are important for rural development. However, there is little information on methods for measuring the process and outcome of social innovation, particularly at the regional level. This study aimed to answer the research question: Which social innovation metrics can be applied to analyze rural development at the regional level? We carried out a systematic review of the literature on factors and indicators of social innovation, assessed the characteristics of social innovation in value-added agricultural production systems in developed countries, and proposed social innovation indicators for evaluating value-added agricultural systems in developing countries. Key elements of the process and outcome dimensions of social innovation were identified and used to generate factors, subfactors, indicators, and subindicators. The literature review showed that more research is needed on the outcomes of social innovation. Future studies should investigate the social transformations promoted by rural tourism and biodiversity valorization.
Number: 2
Keywords: Agriculture; Développement rural; Europe; Innovation sociale; Mesure d'impact; Réservé UdeM; Transformations sociales

University Medialabs: New Learning Spaces for Educational Innovation - Almaraz-Menéndez, Fernando; Martín-García, Teresa; López-Esteban, Carmen (Journal of Strategic Innovation and Sustainability, 2021)
Higher Education Institutions, like many other organizations, are facing pressure from the development of digital technologies as a push towards the digitization of their activities and towards a type of change that some describe as disruptive and that forces them to review their processes and structures. This article describes the case of the medialab of the University of Salamanca, MEDIALAB USAL, as an experience of new learning space in higher education. Its origin is explained from the experiences of citizen technology laboratories and experimental laboratories at the point of intersection between Art, Science and Technology. Its structure and working methods are explained, and its activities are illustrated through the description of four educational innovation projects based on different digital technologies: a mathematics didactics project using AppInventor, Wikipedia as a tool for knowledge generation, Arduino for innovation in the teaching of Fine Arts and a university Hackathon as an activity to introduce students to social and entrepreneurial innovation processes.
Number: 4
Keywords: Collaboration; Durabilité; Europe; Innovation pédagogique; Innovation sociale; Laboratoire vivant; Libre accès; Living Labs; Rôle des universités; Technologies; numérique

8 funding opportunities for social innovators - Balamatsias, Grigorios (Social Innovation Academy, 2018)
Funding opportunities for social innovators are endless. If you have a good idea or initiative already, money can follow if you know where to look for.
Keywords: Europe

House of Innovation - Social Innovation Scholarship - Stockholm School of Economics (Stockholm School of Economics, 2022)
The purpose of the social innovation scholarship is to enable SSE students to pursue opportunities within the realm of social entrepreneurship and social innovation. It represents an opportunity for SSE students to spend the summer working for and supporting a social entrepreneur or NGO somewhere in the world. It is a chance to leverage their business skills to create real change.
Keywords: Bourses de stages; Europe; Université

La marchandisation du monde associatif - Langlet, Marianne (Érès, 2021)
Conclusion du chapitre: L’investissement à impact social cherche à se réaliser et teste différents outils. Si son action concrète reste à ce jour faible, son idéologie infuse. Et avec elle l’idée que le marché répond mieux aux besoins sociaux que la subvention publique et la solidarité nationale. Autour de cette approche, des acteurs émergent pour parvenir à mesurer et convertir en indicateurs financiers les activités associatives, sociales et écologiques. Des agences se développent, notamment sur la mesure d’impact, pour nourrir ce nouveau marché en puissance. S’il est bénéfique pour les investisseurs qui y gagnent de l’argent et une belle image, il est destructeur pour les politiques sociales dont l’objectif ne peut être la recherche d’une rentabilité financière.
Keywords: Europe; Réservé UdeM; Éthique

Quand science et innovation sociale s’ allient - Rullac, Stéphane; Maeder, Pascal (REISO. Revue d'information sociale, 2021)
Des aides financières encouragent l’innovation scientifique en Suisse. Le domaine social est désormais aussi concerné. Comment présenter sa requête pour améliorer ses chances de décrocher un financement fédéral ? Repères et conseils.
Keywords: Europe; Libre accès

Innovation sociale - Commission européenne (2021)
L'innovation sociale consiste à élaborer de nouveaux projets, services et modèles afin de mieux répondre aux questions sociales. Les citoyens et les partenaires du secteur privé, notamment la société civile, sont invités à apporter leur contribution pour améliorer les services sociaux.
Keywords: Europe; Libre accès; Politiques publiques

innovation sociale - IATE European Union Terminology (IATE European Union Terminology, 2009)
conception et mise en œuvre de réponses créatives aux besoins sociaux
IATE - Entry ID 3501971
Keywords: Bases de données terminologiques; Europe; Libre accès

¿Son las universidades socialmente responsables? - Valle, Maria Belén Arias; Berbegal-Mirabent, Jasmina; Marimon-Viadiu, Frederic (education policy analysis archives, 2021)
The importance of university social responsibility (USR) is given by the commitment assumed by the university towards its stakeholders. This study aims at providing new insights on this topic, by analyzing the level of performance in USR that universities communicate. To this end, a structured procedure in five phases is proposed, analyzing elements of the strategic direction and considering the use of USR indicators which are grouped in the four main areas of impact (organizational, educational, cognitive and social). To do this, a qualitative approach has been followed, supported by the use of text analysis software as well as by frequency and spider diagrams. To illustrate its use and the type of analysis it allows, the procedure is applied to the case of the Catalan higher education system, presenting the results at different levels. The study ends with the discussion of the implications, a list of recommendations and suggestion for future works.
Number: January - July Accès libre
Keywords: Europe; Libre accès; Rôle des universités

The social impact of universities: assessing the effects of the three university missions on social engagement - Carl, Johannes; Menter, Matthias (Studies in Higher Education, 2021)
Whereas the economic impact of universities is undisputed, the social impact of universities remains vague. The purpose of this paper is to examine whether and how universities influence firms’ social engagement. Based on survey data of more than 7,000 German firms, our results reveal that universities positively affect firms’ social engagement mainly through teaching activities. Hence, our findings give impetus to a reinforcement of the university mission ‘teaching’ as a central lever for social change and increased social awareness as well as to a reorientation of the third university mission toward social needs. This paper thereby contributes to our understanding of the changing missions and values of universities and adds to the literature by exploring the underlying mechanisms of the social impact of universities. We conclude the paper with fruitful future avenues of research.
Number: 5
Keywords: Europe; Réservé UdeM; Rôle des universités

Des aides financières encouragent l’innovation scientifique en Suisse. Le domaine social est désormais aussi concerné. Comment présenter sa requête pour améliorer ses chances de décrocher un financement fédéral ? Repères et conseils. - Rullac, Stéphane (Revue d'information sociale, 2021)
Des aides financières encouragent l’innovation scientifique en Suisse. Le domaine social est désormais aussi concerné. Comment présenter sa requête pour améliorer ses chances de décrocher un financement fédéral ? Repères et conseils
Keywords: Europe; Magazine; Suisse

Inclusion in social innovation through the primary and secondary use of technology: a conceptual framework - Oomens, I. M. F.; Scholten, C. (International Review of Applied Economics, 2020)
People with disabilities are an important actor and target group in social innovation initiatives worldwide, as there is a clear need for better inclusion of this group in society. A way to improve the inclusion of people with disabilities is the development of assistive technology. In practice, people with disabilities often use technologies of which the primary use is not that of an assistive technology. They use the technology for a different use and context than the developer intended – termed 'secondary use'. The current paper studies the factors that are needed to make the secondary use of technology a success. First, a literature review and explorative study in the Netherlands are performed, after which a framework on the secondary use of technology for inclusion, specifically for people with disabilities, is developed.
Number: 5
Keywords: EDI; Europe; Personnes en situation de handicap; Réservé UdeM

Technology-transfer offices and academic open labs as different types of organizational intermediaries in science-society relationships - Mérindol, Valérie; Gallié, Emilie Pauline; Capdevila, Ignasi (Gestion 2000, 2018)
Cet article étudie les caractéristiques des structures de transfert technologique et des laboratoires d’innovation ouverte gérés par les universités et organismes de recherche. Il compare leurs rôles comme intermédiaires des relations science–entreprises en fonction des modes 2 et 3 de production des connaissances proposés par Etzkowitz & al (1997) et Carayannis & al (2009). Basée sur une comparaison de cas multiples en France, nous analysons leur rôle dans le développement des relations science-entreprise. Cet article identifie aussi les modes de coordination entre ces deux types d’intermédiaires. Dans certains cas, ils coordonnent leurs activités de manière ponctuelle alors que, dans d’autres cas, la complémentarité de leurs activités s’organise sur la durée.
Number: 2 Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 1 Publisher: Association de Recherches et Publications en Management
Keywords: Europe; France; Réservé UdeM; Rôle des universités

Vers un « modèle français » de régulation de l’intelligence artificielle fondé sur l’innovation sociale ? - Chevret-Castellani, Christine; Labelle, Sarah (Communication, technologies et développement, 2021)
Nous présentons dans cet article les résultats d’une enquête sur les politiques publiques de régulation de l’intelligence artificielle et en particulier sur les stratégies mises en œuvre dans des cadres socio-politiques aux échelles nationales, européennes et internationales. La France a créé des instances dans lesquels des « frottements » entre acteurs différents sont possibles, comme les groupes d’experts ou le Partenariat Mondial sur l’Intelligence Artificielle. Nous considérons que le travail de la part de l’ensemble des groupes sociaux, impliqués dans les instances que nous observons, est consubstantiel à la régulation. Les acteurs publics et privés s’organisent pour échanger et interagir de façon structurée, notamment par la mise en place de ces instances, comme le PMIA. Les dispositifs et instruments, auxquels les différents acteurs participent, contribuent à conférer un sens aux activités de régulation. Notre hypothèse repose sur l’émergence d’un « modèle français » de la régulation qui tend à promouvoir la « confiance » et dont le sens est de parvenir à l’acceptabilité sociale de l’IA.
Number: 10 Publisher: La Chaire Pratiques émergentes en technologies et communication pour le développement
Keywords: Europe; France; Intelligence artificielle; Internet; Modèle de réglementation; Politiques publiques; Réservé UdeM

Why are social enterprises good candidates for social innovation? Looking for personal and institutional drivers of innovation - Tortia, Ermanno C.; Degavre, Florence; Poledrini, Simone (Annals of Public and Cooperative Economics, 2020)
The last few years witnessed theoretical and practical contributions to the field of social innovation and social enterprise. However, analysis of the interplay between these two different realms is still limited. This article aims to fill some gaps in this respect. We deal with historical reconstruction of the concept of Social Enterprise and Social Innovation, and their conceptual premises. We consider the process of creation of social innovation in social enterprises. As members’ motivations, ownership rights and governance rules in social enterprises create a new relational context and new routines, which are germane to the production of social knowledge and deliberation, social innovation can be considered one of the main outcomes of this setting. Social motivations, collective action of a cooperative kind, multistakeholder governance and socialization of resources, and their interplay are singled out as main drivers of innovation. Social innovation is seen as akin to novelty in social interaction, a non-standardized and non-standardizable outcome of the operation of this organizational form.
Number: 3
Keywords: Entreprise; Europe; Innovation sociale; Mise en valeur; Réservé UdeM

Our impact - Schwab Foundation for Social Entrepreneurship (Schwab Foundation for Social Entrepreneurship, 2021)
The Schwab Foundation for Social Entrepreneurship launched its 2020 Impact Report which showcases the collective impact of the Schwab Foundation social entrepreneur community.
Keywords: Europe; Mesure d'impact; OBNL

Shaping social innovation in local communities: The contribution of intermediaries - Cibin, Roberto; Robinson, Sarah; Teli, Maurizio; Linehan, Conor; Maye, Laura; Csíkszentmihályi, Christopher (Proceedings of the 11th Nordic Conference on Human-Computer Interaction: Shaping Experiences, Shaping Society, 2020)
Participatory social innovation projects often involve the coming together of design researchers, community development groups, and community members to develop (often technological) solutions to social problems or challenges. “Intermediaries” are specific individuals and organisations who contribute to these projects by translating intentions, values and experiences between design researchers and communities. Previous research has not yet critically examined the role of intermediaries in such projects. This paper does so in a project carried out in rural areas of Europe, which sought to test and develop a technology to support the creation of FM community radio stations in isolated areas. We present the project as a biography of infrastructures to provide an account of intermediaries’ interactions during the project's unfolding. We find that how intermediaries shape the social base and ends of the project, and the interpretation of the technology involved, is influenced by their position, goals, and relationships in the process.
Keywords: Communauté d'innovation; Europe; Libre accès

Knowledge, Learning and Innovation: Research Insights on Cross-Sector Collaborations - Ratten, Vanessa; Braga, Vitor; Marques, Carla Susana (Contributions to Management Science. New York: Springer Nature, Springer, 2018)
Twelve papers examine knowledge, learning, and innovation in order to enhance competitiveness. Papers also explore perspectives of cross-sector collaboration, intrafirm and interfirm connections, gender, and relational marketing. Papers discuss knowledge, learning, and innovation–research into cross-sector collaboration; entrepreneurial competencies and firm performance in emerging economies–a study of women entrepreneurs in Malaysia; whether online cocreation influences lead users' and opinion leaders' behaviors; knowledge and innovation in Portuguese enterprises; social ties and human capital in family small- and medium-sized entrepreneurial internationalization; perceived social support and social entrepreneurship–gender perspectives from Turkey; entrepreneurship challenges and gender issues in the African informal rural economy; the construction of a professional identity of a female entrepreneur; knowledge creation and relationship marketing in family businesses–a case-study approach; the gender question and family entrepreneurship research; a composite-index approach to detecting reporting quality–the case of female executives in family firms; and influencing factors in customers' intention to revisit resort hotels–the roles of customer experience management and customer value. Ratten is Associate Professor at La Trobe University. Braga is Associate Professor of the Technology and Management at the Polytechnic Institute of Porto. Marques is Assistant Professor and Coordinator of the Innovation, Markets and Organization Research Group in the Centre for Transdisciplinary Development Studies at the University of Tras-os-Montes and Alto Douro. No index.
Pages: xvii, 207
Keywords: Europe; Innovation; Réservé UdeM; Étude de cas

The role of social innovation in criminal justice reform and the risk posed by proposed reforms in England and Wales - Fox, Chris; Grimm, Robert (Criminology & Criminal Justice: An International Journal, 2015)
The UK government has called for a rehabilitation revolution in England and Wales and put its faith in market testing. It hopes this will lead to greater innovation, resulting in reductions in re-offending while also driving down costs. However, many of the most innovative developments in criminal justice over recent decades have come through social innovation. Examples include restorative justice and justice reinvestment. In this article we argue that while social innovation will respond to some extent to conventional economic policy levers such as market testing, de-regulation and the intelligent use of public sector purchasing power it is not simply an extension of the neo-liberal model into the social realm. Social innovation, based on solidarity and reciprocity, is an alternative to the logic of the neo-liberal paradigm. In policy terms, the promotion of social innovation will need to take account of the interplay between government policy, social and cultural norms and individual and social capacity. Current proposals for reforming the criminal justice system may not leave sufficient scope to develop the conditions for effective social innovation.
Number: 1
Keywords: Europe; Réservé UdeM

From Research to Numbers: Role of Universities in Social Innovation - Cunha, Jorge; Ferreira, Carla; Araújo, Madalena; Benneworth, Paul (Innovations in Industrial Engineering, 2022)
Commonly, social innovation is defined as new ideas proposals to the needs of humans. However, there is a lack of a well-definition comprehensive leading the fragmentation of field research. On the other hand, the contribution of universities for social innovation development is still less investigated. In this sense, this study intends to explore interrelations between universities and social innovation in relation to different lines of investigation employed. For this, a content analysis was applied to results obtained by Cunha et al. [1]. Five categories of analysis were defined. Findings revealed that there are a number of studies that applied qualitative research to investigate practical examples of social innovation inside of universities and few empirical studies. A link among keywords social innovation, higher education, and social entrepreneurship was found. Furthermore, the analysis showed that there is not a leader country but a distribution across several countries, where Spain and United Kingdom stand out. Thus, this result suggests that it would be helpful to develop an instrument to measure academics’ engagement with social innovation research and practice. In addition, this research contributes to current knowledge regarding the role of universities in social innovation model, providing new theoretical and practical insights of investigation.
N'AVONS PAS ACCÈS
Keywords: Europe; Rôle des universités

The impact of corporate social responsibility on innovation in small and medium‐sized enterprises: The mediating role of debt terms and human capital - Santos‐Jaén, José Manuel; Madrid‐Guijarro, Antonia; García‐Pérez‐de‐Lema, Domingo (Corporate Social Responsibility & Environmental Management, 2021)
The aim of this paper is to study the influence of corporate social responsibility (CSR) over small and medium‐sized enterprise (SME) innovation and the effect of two mediating variables, debt terms and human capital. Based on a sample of 2825 Spanish SMEs and applying a structural equations modeling, the results demonstrate that the effect of CSR on innovation is mediated by debt terms and by good human resource practices. Part of the positive effect of CSR on innovation occurs through these two variables, which, alone, positively and significantly affect innovation in SMEs. Consequently, the positive effect of CSR practices on debt terms through a decrease in asymmetric information goes further, also having repercussions on innovation. Additionally, the suitable development of human resource practices based on strategies oriented toward CSR allow companies to carry out greater and more efficient innovative activities. This paper contributes to the CSR literature considering the human resource management and the debt access in the relationship between CSR and innovation. The findings reveal important implications for policy makers and managers. For the former, the results show that it would be interesting to carry out actions aimed at assisting SMEs, especially those with fewer resources available, to implement a suitable CSR strategy, supporting sustainable development in SMEs. And, for the latter, CSR‐oriented innovation has proven to be a valuable strategy for more efficient SMEs management because of the multiple competitive advantages it generates.
Number: 4
Keywords: Europe; Responsabilité sociétale des entreprises; Réservé UdeM

Consommation et innovation sociale inversée dans l’espace francophone : quand les consommateurs participent à l’amélioration des conditions de vie des producteurs - Ledjou, Jean-Michel; Randrianasolo-Rakotobe, Hanitra (Revue Organisations & territoires, 2021)
L’Union européenne comme les pouvoirs publics français peinent à trouver des solutions aux crises agricoles. Le secteur laitier n’échappe pas à la règle. En 2016, quelque 7000 consommateurs français ont activement participé à la coconstruction d’une filière laitière guidée par un objectif social : améliorer les conditions de vie des producteurs. L’innovation repose ainsi sur une nouvelle méthode de fixation du prix de vente du lait conditionné. Nous montrerons par cet exemple ainsi que par d’autres exemples en France que ce type de coconstruction constitue une innovation sociale inversée. Cette dernière tire parti d’un demi-siècle d’apprentissage fondé sur l’institutionnalisation du « caractère équitable » d’un bien, lequel est au coeur du commerce équitable Nord-Sud. Le label « équitable » n’est donc plus réservé aux seuls pays en développement. Nous analyserons également la portée des technologies numériques (TN) qui réduisent la « distance sociale » entre producteurs, implantés au Sud ou au Nord, et consommateurs. Ainsi, les consommateurs peuvent arbitrer à travers les TN, et ce, dans plusieurs filières.
Number: 1
Keywords: Commerce équitable; Europe; Libre accès

Social Innovation at Technical Universities – State of the Art - Berg, Julia; Leicht-Scholten, Carmen (Proceedings of ISPIM Conferences, 2021)
This paper presents the state of the art in promoting social innovation at five leading technical universities in Europe. We assess how these leading technical universities implement social innovation in their strategies, teaching, and research. The results show that all universities highlight the importance of finding solutions to global challenges and addressing Responsible Research and Innovation (RRI) as a fundamental university strategy for example by promoting social innovation. Moreover, all address the universities’ need to contribute to sustainability and the Sustainable Development Goals. However, social innovation does not play an important role in research and teaching as the results show that social innovation has so far been little addressed in research and teaching. Based on the political framework in the five European countries, we draw up conclusions for technical universities
N'AVONS PAS ACCÈS
Keywords: Europe; Rôle des universités

Contribution of Higher Education Institutions to Social Innovation: Practices in Two Southern European Universities - Monteiro, Sílvia; Isusi-Fagoaga, Rosa; Almeida, Leandro; García-Aracil, Adela (Sustainability, 2021)
The interactions between the higher education sector and society and industry have been attracting increased attention in terms of ways to develop social innovation solutions to societal problems. Despite calls from politicians and the existence of some guidelines, we know little about how higher education could incorporate social innovation activities into its structure and missions. This study examines some practice experiences in two southern European public universities in Portugal and Spain. We show that the third mission of universities, which includes social innovation, is both linked to the first two missions of teaching and research, depending on the university’s historical and social context. The high dependence of higher education institutions on economic returns increases the importance of political action to drive the development of social innovation activities. This conditioning factor seems to be intrinsic to some of the barriers that have been identified, such as lack of legitimization and recognition of social innovation practices at the formal governmental level.
Number: 7 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: Europe; Libre accès; Rôle des universités

Blockchain et Intelligence Collective pour le Design des Connaissances de l'Internet des Objets: Modélisation du pouvoir d'agir des objets connectés - Szoniecky, Samuel (Proceedings of the 1st International Conference on Digital Tools & Uses Congress, 2018)
Cet article est une réponse prospective aux besoins de l'Internet des Objets en termes de simplicité d'utilisation, de gestion de la sécurité et de préservation de la vie privée. Nous proposons de satisfaire ces besoins à travers une plateforme d'intelligence collective utilisant des cartographies sémantiques en réalité augmentées pour récolter les interactions des utilisateurs avec des objets connectés. L'association de l'intelligence collective et des cartographies sémantiques permet d'envisager un design de connaissances où les capacités d'action des objets connectés sont facilement compréhensibles et modifiables par les utilisateurs. Dans ce dispositif, les technologies de blockchain sont utilisées pour partager en sécurité l'expression des utilisateurs et ainsi augmenter la confiance dans l'Internet des Objets et par la même contribuer au développement d'une réflexivité collective sur les usages de ces écosystèmes sociotechniques.
Keywords: Europe; France; Internet des objets; Mesure de la perception; Réservé UdeM

Research with a Solidarity Clinic: Design Implications for CSCW Healthcare Service Design - Vlachokyriakos, Vasilis; Crivellaro, Clara; Kouki, Hara; Giovanopoulos, Christos; Olivier, Patrick (Computer Supported Cooperative Work-the Journal of Collaborative Computing and Work Practices, 2021)
This paper reports on a long-term collaboration with a self-organised social clinic, within solidarity movements in Greece. The collaboration focused on the co-creation of an oral history group within the social clinic, aiming to record and make sense of a collection of digital oral histories from its volunteers and volunteers-doctors. The process aimed to support reflection and shape the future of the clinic's ongoing social innovation and to transform institutional public health services. Positioning the work of solidarity movement as designing social innovation, the work contributes to CSCW and 'infrastructuring' in Participatory Design aspiring to support social activism and social transformation processes. More specifically, through our empirical insights on the process of infrastructuring an oral history group within a social movement; and related insights about their ongoing participatory health service provision-we provide implications for CSCW concerned with its role in institutional healthcare service transformation.
Place: Dordrecht Publisher: Springer WOS:000665666500001
Keywords: Computer Supported Cooperative Work (CSCW); Europe; Participatory Design; Réservé UdeM

Social Innovation and University Intellectual Property: Insights from the UK and Mexico - McDonagh, L.; Bonadio, E.; Alba Betancourt, A. (European Intellectual Property Review, 2020)
University intellectual property policies, and the accompanying strategies for incubation of IP via licensing and spin outs, have not received much analysis from academic lawyers. Moreover, despite the success of universities in the UK at generating income from IP, not much is known about how transferable this success is when considered in the light of a rapidly growing middle-income developing economy such as Mexico’s. In this article we analyse critically some of the key tenets of IP policies at universities in the UK to identify what the key legal principles underpinning university innovation are. We further consider the potential application of these principles in Mexico, where so far only a limited number of universities have developed IP policies and strategies in line with the incubator model. We explain how universities in Mexico could implement these research findings in their own IP policies. We further note that the mere provision of an IP policy is not a panacea – on its own it is insufficient for ensuring technology transfer and it may even encourage unnecessary patenting. Further investment in infrastructure and in establishing a culture of incubation and entrepreneurship is also required.
Publisher: Sweet and Maxwell
Keywords: Amérique latine; Europe; Libre accès; Propriété intellectuelle; UK

Playing with the Rules of the Game: Social Innovation for Urban Transformation - Thompson, Matthew (International Journal of Urban and Regional Research, 2019)
Innovation is perhaps the buzzword in local economic development policy. Associated narrowly with neoliberal ideas, conventional notions of innovation—like its capitalocentric counterparts, enterprise and entrepreneurialism—may promise higher productivity, global competitiveness and technological progress but do not fundamentally change the ‘rules of the game’. In contrast, an emerging field reimagines social innovation as disruptive change in social relations and institutional configurations. This article explores the conceptual and political differences within this pre‐paradigmatic field, and argues for a more transformative understanding of social innovation. Building on the work of David Graeber, I mobilize the novel constructs of ‘play’ and ‘games’ to advance our understanding of the contradictory process of institutionalizing social innovation for urban transformation. This is illustrated through a case study of Liverpool, where diverse approaches to innovation are employed in attempts to resolve longstanding socio‐economic problems. Dominant market‐ and state‐led economic development policies—likened to a ‘regeneration game’—are contrasted with more experimental, creative, democratic and potentially more effective forms of social innovation, seeking urban change through playing with the rules of the game. I conclude by considering how the play–game dialectic illuminates and reframes the way transformative social innovation might be cultivated by urban policy, the contradictions this entails, and possible ways forward.
Number: 6 Num Pages: 1168-1192 Place: Oxford, United Kingdom Publisher: Blackwell Publishing Ltd. Section: Articles
Keywords: Europe; Réservé UdeM; UK

NESTA
We bring bold ideas to life to change the world for good.
Carte d'inbformation Type d'organisme : Organisme public non ministériel Échelle géographique : Royaume-Uni Type de contenu et outils proposés : - Méthodes d'innovation - Le pôle découverte - Ateliers - Investissements à impact - Analyse des données, Intelligence collective, Preuve et expérimentation, Arts et économie créative, Design et technologie, Sciences du comportement - Newsletter - Laboratoire de croissance de l'innovation - Stimuler et Accompagnemer l'innovation - Évènements Blog - Rapports (bibliothèque de recherche et d'analyses - Boîte à outils et guides Public visé : Décideurs politique, éducateurs, industries créatives Nesta est un organisme en soutien à l'innovation sociale soutenu par la Young Foundation.
Keywords: Europe; Organisme de soutien

Livin - Virtual Community Platform
Carte d'information Type d'organisme : Initiative européenne Échelle géographique : Europe Type de contenus et outils proposés - Communauté en ligne - Ateliers sur place et de dialogues en ligne - Évènements - Réseau Public visé : Citoyennes/citoyens, entreprises, politiques
Keywords: Europe; Organisme de soutien

RRI Tools
Carte d'information Type d'organisme : Consortium Échelle géographique : Europe Type de contenu et outils proposés - Boîte à outils - Formations - Communauté - Actualités - Blog - Forum - Conférences Public visé : tous les acteurs (des chercheurs et innovateurs individuels aux institutions et aux gouvernements)
Keywords: Europe; Organisme de soutien

The Co-create handbook - Co-create consortium
Consortium européen "Over the past 30 years, almost every aspect of doing design has changed. We still seem to be in the middle of a transition to greater entanglement and complexity, but with greater involvement of people and, hopefully, more value contributed by the design capabilities of many. We can anticipate these uncertainties with hope or fear. But if we can use design thinking, making, and enacting to visualize and explore the future together, then we will be able to harness our collective creativity to serve our collective dreams." * *Co-creation and the landscapes of design, Elizabeth B.-N. Sanders & Pieter Jan Stappers www.tandfonline.com/doi/abs/10.1080/15710880701875068
Ressource pertinente pour expliquer la cocréation et le codesign. Procure également des outils pour aider à l'idéation, dialogue et maillage, tel qu'une cartographie des parties prenantes.
Keywords: Co-création; Europe; Idéation; dialogue et maillage

SHIFT Design (Shift)
Shift's approach to using design thinking for collective impact.
Carte d'information Type d'organisme : Organisme de bienfaisance Échelle géographique : Royaume-Uni Type de contenu et outils proposés : - Rapports, articles et vidéos - Nouvelles Public visé : Organismes communautaire, entrepreneur.e.s
Keywords: Europe; Organisme de soutien

Eureka
Carte d'information Type d’organisme : Association | Entité juridique internationale à but non lucratif de droit belge Échelle géographique : Europe, 18 pays | puis 48 pays en Europe et au-delà** Type de contenu et outils proposés - Programme Clusters pour faciliter le financement des projets de R&D à moyen et long terme - Eurostars : instrument de financement pour soutenir les PME innovantes et les partenaires de projets (grandes entreprises, universités, organismes de recherche et autres types d’organisations) - Projets de réseau : programme de coopération original, flexible et ascendant d’Eureka; appels à projets bilatéraux par thématiques - Globalstars : initiative de coopération mondiale permettant aux organismes de financement nationaux de coordonner et de consacrer des fonds pour des appels à projets bilatéraux ou multilatéraux avec des pays extérieurs au réseau Eureka - Programme de préparation à l’investissement pour les PME de haute technologie financé par la commission européenne en association avec Eureka (programme de préaparation incluant wébianire, cours en ligne gratuits, bootcamps, évaluation avec les pairs, ateliers, académies de coaching et opportunités de présentation). Infos pour le Canada : Les organisations canadiennes participant à des projets internationaux de R&D sont éligibles à un financement par le biais de nos projets de réseau, de nos programmes Globalstars, Eurostars et Clusters. Si vous êtes basé au Canada et que vous recherchez du financement pour un projet de R&D, votre premier point de contact est le Conseil national de recherches du Canada (CNRC) . Le CNRC soutient les organisations canadiennes intéressées par la collaboration internationale en leur donnant accès à l'expertise et en soutenant leur croissance. Public visé : PME, grandes entreprises, universités, organismes de recherche et autres types d’organisations
Keywords: Europe; Organisme de soutien

Communauté de la Fabrique des Mobilites - Living labs
Réseau francophone des living labs. Voir également, Commission permanente de coopération franco-québécoise (CPCFQ) du Consulat général de France à Québec : https://quebec.consulfrance.org/Commission-permanente-de-cooperation-franco-quebecoise-CPCFQ
Carte d'information Type d’organisme : Association Échelle géographique : France-Québec Type de contenu et outils proposés - Les living labs en France et au Québec (les lieux) - Ressources : guide méthodologique pour LL - Présentation en ligne de colloques living labs - Bibliothèque de ressources de la Fabrique des Mobilités - Mobilisation en innovation ouverte - Ententes : (accords inter-gouvernementaux franco-québécois, universitaire, technique et industrielle, organismes de recherche | Exemple : CNRS - FRQ Public visé : Communautés du Québec
Keywords: Europe; Organisme de soutien

ZSI - Centre for Social Innovation (ZSI - Centre for Social Innovation)
The Centre for Social Innovation (ZSI) is pioneering social innovation since 1990, collaborating in international networks to lift the notion of social innovations – in the public, politics, business and civil society – on a par with technological and economic innovations.
Carte d'information Type d’organisme : Institut privé à but non lucratif de sciences sociales appliquées Échelle géographique : Autriche Type de contenu et outils proposés - Recherche - Évaluation, suivi et conseils politiques - Transfert de connaissances et mise en réseau (de l'espace européen de la recherche et l'innovation dans les pays tiers et les régions du monde entier - Coordination et accompagnement Public visé : Organisations internationales partenaires de l'UE
Keywords: Europe; Organisme de soutien

Sozialforschungsstelle | Technische Universität Dortmund (TU Dortmund)
Die 1946 gegründete Sozialforschungsstelle Dortmund (sfs) ist ein international profiliertes Institut anwendungsorientierter sozialwissenschaftlicher Arbeit
Carte d'information Type d’organisme : Centre de recherche universitaire Échelle géographique : Allemagne Type de contenu et outils proposés - Recherche sociale, processus d'innovation sociale et technologique - Recherche sur le travail, co-création, co-construction des processus de changment - Questionne question des conditions et perspectives de réalisation d'un développement économiquement, écologiquement et socialement durable. Public visé :* Étudiant.e.s / Chercheur.e.s
Keywords: Europe; Organisme de soutien

Skoll Centre for Social Entrepreneurship | About | Oxford Saïd
**Carte d'information** Type d’organisme : Centre de recherche universitaire Échelle géographique : Royaume-Uni Type de contenu et outils proposés - Programmes d'éducation internationaux - Évènements : forum mondial de Skoll sur l'enrtepreunariat social, semaine des systèmes - Bourse Skoll - Impact Lab - Récompenses, prix - Subventions de recherche - Podcast - Blog, Revue annuelle - Nouvelles et actualités - Recherche : Observatoire du changement des systèmes, Initiative d'Oxford pour inspirer la diversité entrepreunariale (OXIFIED) Public visé : Entrepreneurs sociaux, chercheur.e.s
Keywords: Europe; Organisme de soutien

Cambridge Centre for Social Innovation (Cambridge Judge Business School)
The Cambridge Centre for Social Innovation (CSI) is a platform for research and engagement with social innovators, academia and policy, that supports social ventures.
Carte d'information Type d’organisme : Centre de recherche universitaire (business school) Échelle géographique : Royaume-Uni Type de contenu et outils proposés - Plateforme de recherche et d'engagement - Prix de l'innovation sociale de Cambridge - Bourses axées sur l'innovation sociales et les entreprises sociales - Programmes de formation / Mentorat - Évènements - Matériel en ligne - Liens et ressources (réseaux sociaux, organismes, ouvrages, guides Public visé : Innovateurs sociaux, universités/universitaires, praticiens, politiques britanniques et à travers le monde, entreprises sociales, entrepreneurs et organisations
Keywords: Europe; Organisme de soutien

Research - Institut für Innovation Management - LMU Munich
Carte d'information Type d’organisme : Institut universitaire Échelle géographique : Allemagne Type de contenu et outils proposés - Recherches sur la dynamique du changement à destination des gestionnaires, des consommateurs et des décideurs / Travaux de recherches avancées - Cours - Ressources recommandés (Ouvrages, littérature) Public visé : Étudiants.e.s / Chercheur.e.s
Keywords: Europe; Organisme de soutien

The Young Foundation (The Young Foundation)
We are a not-for-profit, UKRI-accredited organisation with a unique understanding the changing role of communities in the 21st century. We build knowledge around the issues people care about, supporting collective, locally-led action and enterprise to improve lives and address shared challenges, and driving social change for stronger communities.
Carte d'information Type d’organisme : OBNL de recherche Échelle géographique : Royaume-Uni Type de contenu et outils proposés - Réseau de recherche par des pairs - Institut d'études communautaires - Rapports de recherches - Nouvelles - Blog - Podcast et vidéos - Évènements - Formations - Soutien aux entreprises - Incubateur d'organismes Public visé : Communautés locales, organisations et décideurs politiques; entreprises
Keywords: Europe; Organisme de soutien

Réseau LiEU (Réseau LiEU)
Connecting business to research
Carte d'information Type d’organisme : Réseau d'Universités Échelle géographique : Belgique Type de contenu et outils proposés - Services de transfert de connaissances KTO - Services adaptés aux besoins et accompagnement personnalisé - Collaboration : Mise en relation Chercheur.e.s/partenaires privés ou publics / facilitateur de partenariats avec les entreprises - Conseils en propriété intellectuelle - PATLIB - Plateformes technologiques : compétences et équipements de pointe à disposition - Offres de technologies pour commercialisation sur le marché - Actualités Public visé : Étudiant.e.s / Chercheur.e.s / Entrepreneurs / Entreprises
Keywords: Europe; Organisme de soutien

Social Innovation Academy
Carte d'information Type d’organisme : Plateforme et programme de formation en ligne co-financé par l'Union européenne Échelle géographique : Europe et monde Type de contenu et outils proposés - Contenus d'apprentissage gratuits - Guide d'apprentissage et Guides d'innovation sociale - Conseils de mentor - Quiz - Cours en ligne, certificats - Stages Public visé : Innovateurs sociaux/entrepreneurs sociaux
Keywords: Europe; Organisme de soutien

Limitless (Limitless)
Carte d'information Type d’organisme : Entreprise privée Échelle géographique : Luxembourg Type de contenu et outils proposés - Stratégies et compétences d'innovation (commercial : accompagnement (Limitless innovation factory) - Outils d'innovation (templates organisationnels) - Social Innovation Academy - programme d'apprentissage en ligne et gratuit - Blog innovation Public visé : Multinationales, OBNL, organismes du secteur public
Keywords: Europe; Organisme de soutien

AFD - Agence Française de Développement
Carte d'information Type d’organisme : Établissement financier public/gouvernemental Échelle géographique : France / Outre-mer français et 115 pays dans le monde Type de contenu et outils proposés - Agences dans le monde : appel d'offres, appels à projets, prêts, dons - Partage d'expertise et assistance technique - Carte des projets emblématiques - Financements - Recherche - Formations - Plateforme e-learning - Actualités - Publications - Portail Open Data - Brand Center Public visé : ONG, États, collectivités, fondations, entreprises
Keywords: Europe; Organisme de soutien

Institut Jean-Baptiste Godin
R&D et transfert en sciences humaines et sociales
Carte d'information Type d’organisme : Centre de transfert en pratiques solidaires et innovation sociale (Association loi 1901) Échelle géographique : Europe / France Type de contenu et outils proposés - Transfert d'expertise sur les territoires de la région Hauts-de-France et largement en France - Espace ressources en ligne en R&D, outils et transfert - Colloques, séminaires Public visé : Organisations ayant des activités et des intérêts dans l'innovation ouverte axée sur les utilisateurs
Keywords: Europe; Organisme de soutien

ENoLL - European Network of Living Labs (European Network of Living Labs)
The European Network of Living Labs (ENoLL) is an international non-profit association which aims to promote and enhance user-driven innovation ecosystems,more precise the Living Labs concept globally.ENoLL focuses on facilitating knowledge exchange, joint actions and project partnerships among its historically labelled +475 members, influencing EU policies, promoting living labs and enabling their implementation worldwide.
Carte d'information Type d’organisme : Organisation internationale à but non lucratif / Réseau de laboratoires vivants / Living Labs network Échelle géographique : Europe Type de contenu et outils proposés - Programmes de renforcement des capacités - Processus de labellisation de haut niveau - Certifications de laboratoires vivants - Groupes de travail orientés vers l'action - Matériel de connaissances : boîte à outils, webinaires, podcasts, ouvrages, cours en ligne - Nouvelles et évènements Public visé : Organisations ayant des activités et des intérêts dans l'innovation ouverte axée sur les utilisateurs.
Keywords: Europe; Organisme de soutien

La marchandisation du monde associatif - Langlet, Marianne (Érès, 2021)
Conclusion du chapitre: L’investissement à impact social cherche à se réaliser et teste différents outils. Si son action concrète reste à ce jour faible, son idéologie infuse. Et avec elle l’idée que le marché répond mieux aux besoins sociaux que la subvention publique et la solidarité nationale. Autour de cette approche, des acteurs émergent pour parvenir à mesurer et convertir en indicateurs financiers les activités associatives, sociales et écologiques. Des agences se développent, notamment sur la mesure d’impact, pour nourrir ce nouveau marché en puissance. S’il est bénéfique pour les investisseurs qui y gagnent de l’argent et une belle image, il est destructeur pour les politiques sociales dont l’objectif ne peut être la recherche d’une rentabilité financière.
Keywords: Europe; Réservé UdeM; Éthique

Quand science et innovation sociale s’ allient - Rullac, Stéphane; Maeder, Pascal (REISO. Revue d'information sociale, 2021)
Des aides financières encouragent l’innovation scientifique en Suisse. Le domaine social est désormais aussi concerné. Comment présenter sa requête pour améliorer ses chances de décrocher un financement fédéral ? Repères et conseils.
Keywords: Europe; Libre accès

House of Innovation - Social Innovation Scholarship - Stockholm School of Economics (Stockholm School of Economics)
The purpose of the social innovation scholarship is to enable SSE students to pursue opportunities within the realm of social entrepreneurship and social innovation. It represents an opportunity for SSE students to spend the summer working for and supporting a social entrepreneur or NGO somewhere in the world. It is a chance to leverage their business skills to create real change.
Keywords: Bourses de stages; Europe; Université

8 funding opportunities for social innovators - Balamatsias, Grigorios (Social Innovation Academy, 2018)
Funding opportunities for social innovators are endless. If you have a good idea or initiative already, money can follow if you know where to look for.
Keywords: Europe

Innovation sociale - Commission européenne
L'innovation sociale consiste à élaborer de nouveaux projets, services et modèles afin de mieux répondre aux questions sociales. Les citoyens et les partenaires du secteur privé, notamment la société civile, sont invités à apporter leur contribution pour améliorer les services sociaux.
Keywords: Europe; Libre accès; Politiques publiques

Avise - Portail du développement de l’économie sociale et solidaire (Avise)
L’innovation sociale continue de faire appel à des définitions plurielles. Une majorité s’accorde à dire qu’elle élabore des réponses nouvelles à des besoins sociaux mal ou peu satisfaits dans tous les secteurs : alimentation, mobilité, énergie, habitat, environnement, santé… Portée par différents acteurs, l’innovation sociale apporte des solutions efficaces à des enjeux complexes auxquels ni l’Etat, ni le marché ne peuvent répondre seuls.
Carte d'information Type d’organisme : Agence collective d'ingénierie Échelle géographique : France Type de contenu et outils proposés - Appels à projets - Accompagnement dans la création d'entreprises de l'ESS (Économie Sociale et Solidaire) - dispositif Fabriques à intiatives - Outils pour les porteurs de projets - Organisme intermédiaire FSE (Fond social européen)** - Actualités - Ressources : ouvrages, liens, vidéos, caratographies Public visé : Institutions publiques, organisations privées, réseaux d'innovation, professionnels de l'accompagnement, élus et techniciens en région L’Avise a pour mission de développer l’économie sociale et solidaire (ESS) et l’innovation sociale en France, en accompagnant les porteurs de projet et en contribuant à structurer un écosystème favorable à leur développement. Il est un équivalent en France du TIESS au Québec
Keywords: Europe; Organisme de soutien

Social innovation in high-quality agricultural systems: metrics for assessing processes and outcomes - Santini Pigatto, Giuliana Aparecida; Brunori, Gianluca (Innovation: The European Journal of Social Science Research, 2021)
Social innovation and high-quality agricultural systems are important for rural development. However, there is little information on methods for measuring the process and outcome of social innovation, particularly at the regional level. This study aimed to answer the research question: Which social innovation metrics can be applied to analyze rural development at the regional level? We carried out a systematic review of the literature on factors and indicators of social innovation, assessed the characteristics of social innovation in value-added agricultural production systems in developed countries, and proposed social innovation indicators for evaluating value-added agricultural systems in developing countries. Key elements of the process and outcome dimensions of social innovation were identified and used to generate factors, subfactors, indicators, and subindicators. The literature review showed that more research is needed on the outcomes of social innovation. Future studies should investigate the social transformations promoted by rural tourism and biodiversity valorization.
Keywords: Agriculture; Développement rural; Europe; Innovation sociale; Mesure d'impact; Réservé UdeM; Transformations sociales

First domino tile in the social innovation process: Idea creation of university students - Yıldırım, Nihan; Ansal, Hacer (2016 Portland International Conference on Management of Engineering and Technology (PICMET), 2016)
Interrelations between creativity, innovativeness and entrepreneurial skills of individuals have long been discussed in the literature. Due to the challenges regarding their measurement, most studies focused on the intentions rather than the outcomes. The idea generation that requires creativity is the first stage of social innovation. The young population's creative potentials in participating social innovation practices deserve a special attention as they play a critical role in the innovativeness and entrepreneurship of societies. This study aims to explore the factors that determine the creative intentions of university students that are important in generating social innovation projects. A structured survey based on the literature was conducted among 600 management and engineering students from 3 universities from the different percentiles of the Entrepreneurial and Innovative University Index for 2012 of the Turkish Ministry of Science, Industry and Technology. The survey included questions on the demographic characteristics, environmental factors, motivators, university/institutional context, perceptions and creative thinking attitudes. By conducting reliability and factor analysis, accuracy and validity of data is tested and the impact factors were identified. Findings reveal that visionary attitude, curiosity, exploration and learning, attitude for own creativity, self-esteem, perception about the learnability of creativity, university and social environment are components of creative thinking intentions of students and some of these factors vary by year of study and university.
Keywords: Entrepreneuriat; Europe; Innovation sociale; Réservé UdeM; Rôle des universités; Université

Des aides financières encouragent l’innovation scientifique en Suisse. Le domaine social est désormais aussi concerné. Comment présenter sa requête pour améliorer ses chances de décrocher un financement fédéral ? Repères et conseils. - Rullac, Stéphane (Revue d'information sociale, 2021)
Des aides financières encouragent l’innovation scientifique en Suisse. Le domaine social est désormais aussi concerné. Comment présenter sa requête pour améliorer ses chances de décrocher un financement fédéral ? Repères et conseils
Keywords: Europe; Magazine; Suisse

Shaping social innovation in local communities: The contribution of intermediaries - Cibin, Roberto; Robinson, Sarah; Teli, Maurizio; Linehan, Conor; Maye, Laura; Csíkszentmihályi, Christopher (Proceedings of the 11th Nordic Conference on Human-Computer Interaction: Shaping Experiences, Shaping Society, 2020)
Participatory social innovation projects often involve the coming together of design researchers, community development groups, and community members to develop (often technological) solutions to social problems or challenges. “Intermediaries” are specific individuals and organisations who contribute to these projects by translating intentions, values and experiences between design researchers and communities. Previous research has not yet critically examined the role of intermediaries in such projects. This paper does so in a project carried out in rural areas of Europe, which sought to test and develop a technology to support the creation of FM community radio stations in isolated areas. We present the project as a biography of infrastructures to provide an account of intermediaries’ interactions during the project's unfolding. We find that how intermediaries shape the social base and ends of the project, and the interpretation of the technology involved, is influenced by their position, goals, and relationships in the process.
Keywords: Communauté d'innovation; Europe; Idéation; dialogue et maillage; Libre accès; Étude de cas

Why Do Publicly Funded Firms Find the University More Useful to Innovate Than Others? Can We Accomplish the RIS3 Target? - Costa, Joana (Regional Helix Ecosystems and Sustainable Growth: The Interaction of Innovation, Entrepreneurship and Technology Transfer, 2020)
The failure of the deterritorialised innovation policy addressing the regions based on the “one-size-fits-all” policymaking made the Research and Innovation Strategies for Smart Specialisation (RIS3) become the Holy Grail of the European cohesion. This policy strategy is part of a multilevel framework, which encompasses national and regional vectors harmonising transversal strategies and combining different aspects to generate a consistent policy mix. This growth strategy will reinforce the existence of an innovative and knowledge-based society, which aims to raise welfare, promote responsible practices, modernise economic activity and spread prosperity.Sustainable growth will optimise the use of resources, boost the efficiency levels, generate competitiveness and respect the environment. Inclusive growth will promote social and territorial cohesion which is sought after in the convergence policy, which has slowed down the pace after the financial crisis.The development of regional competitive advantages will rely on the establishment of relevant linkages between the Academia and the private institutions in knowledge creation and transfer. In this vein, the University is expected to play a central role, facing important challenges and requiring transformations, mostly in the case of less favoured regions.Productivity raise, construction of comparative advantages, market consolidation and profit maximisation, required to avoid the obsolescence of firms, will rely in the prosecution of innovative activities. Despite being risky, these activities are sought by firms as a source of economic performance increase, being the building blocks of a profit maximisation strategy. The velocity at which innovation occurs will differ among industrial sectors due to their singularities along with other firm structural characteristics, still, those who perform innovative activities are more prone to achieve higher standards of turnover growth and profits. The organisational competences concerning human capital, knowledge absorption, accumulation and diffusion will enhance the innovation capabilities, thus generating advantages. In this path, Universities will be determinant as they may leverage the success of the entrepreneurial innovativeness throughout the provision of relevant knowledge, productive techniques and methods. Absorbing, transforming and exploiting the general knowledge provided by the University will be the firms’ incumbency which will reflect the speed and the success of the individual’s innovative performance. Considering the reinforced role of the Academia as a knowledge producer and therefore inside the innovation process, the existence of incipient connections with firms will be unbearable.What enables and hinders University-firm linkages is, so far, overlooked in the literature demanding for the comprehensive analysis, in particular the causes of its failure, and the accurate policy mix that overcome the situation is vital for a successful RIS3.The singularities of this policy framework require redirection of the tools and actions to be taken such as incentives, grants, loans and subsidisation strategies. Empirical results shed light to the significant difference observed in the classification of the University as a source of information for innovation between public monies recipients and other firms. Among public funding beneficiaries, the Academia is an important source of knowledge to draw upon; conversely, for the other firms, it seems of poor importance the knowledge conveyed in the contact. In general, firms fail to consider the University as a relevant source of information for innovation, which seems to be incompatible with the establishment of smart specialisation strategies.These unexplored connections, which pledge the success of the present innovation policy, and reinforce the importance of its appraisal to fully understand the determinants of University-firm linkages and its connection to public subsidisation, encompassing the identification of the most effective beneficiaries. The econometric estimations, relying on the CIS, were run considering a panel of firms operating in Portugal, which provides the empirical evidence for a moderate innovation milieu which is poorly done so far as most of the studies focus on innovation leader.The findings reinforce the existence complementarities among policy instruments and highlight that new avenues of research should explore other policy instruments such as open innovation frameworks.
Keywords: Europe; Idéation; dialogue et maillage; Innovation ouverte; Réservé UdeM

Technology-transfer offices and academic open labs as different types of organizational intermediaries in science-society relationships - Mérindol, Valérie; Gallié, Emilie Pauline; Capdevila, Ignasi (Gestion 2000, 2018)
Cet article étudie les caractéristiques des structures de transfert technologique et des laboratoires d’innovation ouverte gérés par les universités et organismes de recherche. Il compare leurs rôles comme intermédiaires des relations science–entreprises en fonction des modes 2 et 3 de production des connaissances proposés par Etzkowitz & al (1997) et Carayannis & al (2009). Basée sur une comparaison de cas multiples en France, nous analysons leur rôle dans le développement des relations science-entreprise. Cet article identifie aussi les modes de coordination entre ces deux types d’intermédiaires. Dans certains cas, ils coordonnent leurs activités de manière ponctuelle alors que, dans d’autres cas, la complémentarité de leurs activités s’organise sur la durée.
Bibliographie_available: 1 Cairndomain: www.cairn.info Cite Par_available: 1 Publisher: Association de Recherches et Publications en Management
Keywords: Europe; France; Réservé UdeM; Rôle des universités; Technologie; Transfert; Valorisation

Knowledge, Learning and Innovation: Research Insights on Cross-Sector Collaborations - Ratten, Vanessa; Braga, Vitor; Marques, Carla Susana (Contributions to Management Science. New York: Springer Nature, Springer, 2018)
Twelve papers examine knowledge, learning, and innovation in order to enhance competitiveness. Papers also explore perspectives of cross-sector collaboration, intrafirm and interfirm connections, gender, and relational marketing. Papers discuss knowledge, learning, and innovation–research into cross-sector collaboration; entrepreneurial competencies and firm performance in emerging economies–a study of women entrepreneurs in Malaysia; whether online cocreation influences lead users' and opinion leaders' behaviors; knowledge and innovation in Portuguese enterprises; social ties and human capital in family small- and medium-sized entrepreneurial internationalization; perceived social support and social entrepreneurship–gender perspectives from Turkey; entrepreneurship challenges and gender issues in the African informal rural economy; the construction of a professional identity of a female entrepreneur; knowledge creation and relationship marketing in family businesses–a case-study approach; the gender question and family entrepreneurship research; a composite-index approach to detecting reporting quality–the case of female executives in family firms; and influencing factors in customers' intention to revisit resort hotels–the roles of customer experience management and customer value. Ratten is Associate Professor at La Trobe University. Braga is Associate Professor of the Technology and Management at the Polytechnic Institute of Porto. Marques is Assistant Professor and Coordinator of the Innovation, Markets and Organization Research Group in the Centre for Transdisciplinary Development Studies at the University of Tras-os-Montes and Alto Douro. No index.
Pour que la collaboration intersectorielle réussisse, il est nécessaire qu'elles partagent les connaissances et l'innovation par le biais d'un processus d'apprentissage. Ouvrage « fournissant de nouvelles perspectives sur les moyens de stimuler la collaboration intersectorielle ». Présentations de plusieurs méthodes unifiant connaissance, apprentisage et innovation | Exemples : entreprises portugaises, PME familiales, économie sociale informelle africaine, perspective de genre en Turquie etc.
Keywords: Europe; Idéation; dialogue et maillage; Réservé UdeM; Étude de cas

Social innovation governance and the role of universities: Cases of quadruple helix partnerships in Italy - Bellandi, Marco; Donati, Letizia; Cataneo, Alessandra (Technological Forecasting and Social Change)
This paper explores the governance of social innovation throughout quadruple helix partnerships between civil society, business, government, and academic actors. Particular attention is given to the participation of universities in such partnerships as an expression of public and community engagement under broad third mission goals. Quadruple helix partnerships may favour the governance of projects aiming at social innovation, but conflicts and drawbacks can hinder the alignment of partners’ contributions. To tackle this issue, we develop a conceptual framework that points out four key phases in such governance processes: i) identification of a common nexus, ii) building of shared strategies, iii) implementation, and iv) learning feedbacks. We apply this framework to three Italian projects under the new EU Urban innovative actions’ program. Different alignment pathways and barriers in the governance process emerge and are discussed. The results show that quadruple helix partnerships for social innovation work smoothly if a solid common nexus between partners is in place. The University is used as a focal actor to understand the mechanisms underpinning each phase and the role it may play in such partnerships.
Keywords: Europe; Gouvernance; Innovation sociale; Partenariat; Quadruple helix approach; Réservé UdeM; Rôle des universités

¿Son las universidades socialmente responsables? - Valle, Maria Belén Arias; Berbegal-Mirabent, Jasmina; Marimon-Viadiu, Frederic (education policy analysis archives, 2021)
The importance of university social responsibility (USR) is given by the commitment assumed by the university towards its stakeholders. This study aims at providing new insights on this topic, by analyzing the level of performance in USR that universities communicate. To this end, a structured procedure in five phases is proposed, analyzing elements of the strategic direction and considering the use of USR indicators which are grouped in the four main areas of impact (organizational, educational, cognitive and social). To do this, a qualitative approach has been followed, supported by the use of text analysis software as well as by frequency and spider diagrams. To illustrate its use and the type of analysis it allows, the procedure is applied to the case of the Catalan higher education system, presenting the results at different levels. The study ends with the discussion of the implications, a list of recommendations and suggestion for future works.
Accès libre
Keywords: Europe; Libre accès; Rôle des universités

Why do universities have little systemic impact with social innovation? An institutional logics perspective - Cinar, Ridvan; Benneworth, Paul (Growth & Change, 2021)
Social innovation has been increasingly regarded as an instrument through which transformative structural change, necessary to address grand societal challenges can be achieved. Social innovations are encouraged by the emergence of innovation systems that support changes not exclusively driven by a techno-economic rationality. In the context of this special issue, there has been both little understanding of social innovation systems within mainstream innovation ecosystem approaches and little analysis of the roles played by universities in social innovation systems. We here focus on the institutional complexity of universities and their field-level dynamics as serving as a potential break on the institutionalisation of social innovation. To deepen our understanding of this, we utilise a literature around institutional logics to foreground characteristics of organisational fields with regard to social innovation. Drawing on empirical data gathered in two public universities located in different countries, we show that in one case the potential of social innovation is undermined by two dominant institutional logics, in the other its permeation across the organisational field is seriously challenged by a more powerful dominant logic. The institutional logic approach is useful to highlighting the barriers to building productive innovation ecosystems incorporating social considerations, and helps to explain the persistent difficulties in reframing ecosystems approaches to reflect wider societal dynamics.
Keywords: Europe; Réservé UdeM; Rôle des universités

The Impact of Societal and Social Innovation: a Case-Based Approach - Lin, Carol Yeh-Yun; Chen, Jeffrey (Springer Singapore, 2016)
Keywords: Asie; Changement systémique; Entrepreneuriat social; Europe; Innovation; Innovation sociale; Innovation sociétale; Mesure d'impact; Parties prenantes; Processus d'innovation; Réservé UdeM; Étude de cas

Analyzing Citizen Participation and Engagement in European Smart Cities - Cortés-Cediel, María E.; Iván, Cantador; Rodríguez, Bolívar Manuel Pedro (Social Science Computer Review, 2021)
With the advent of smart cities (SCs), governance has been placed at the core of the debate on how to create public value and achieve a high quality of life in urban environments. In particular, given that public value is rooted in democratic theory and new technologies that promote networking spaces have emerged, citizen participation represents one of the principal instruments to make government open and close to the citizenry needs. Participation in urban governance has undergone a great development: from the first postmodernist ideals of countering expert dominance to today’s focus on learning and social innovation, where citizen participation is conceptualized as co-creation and co-production. Despite this development, there is a lack of research to know how this new governance context is taking place in the SC arena. Addressing this situation, in this article, we present an exhaustive survey of the research literature and a deep study of the experience in participative initiatives followed by SCs in Europe. Through an analysis of 149 SC initiatives from 76 European cities, we provide interesting insights about how participatory models have been introduced in the different areas and dimensions of the cities, how citizen engagement is promoted in SC initiatives, and whether the so-called creative SCs are those with a higher number of projects governed in a participatory way.
Num Pages: 592-626 Place: Thousand Oaks, United States Publisher: SAGE PUBLICATIONS, INC.
Keywords: Co-création; Co-production; Europe; Modèle participatif; Nouvelles technologies; Projets participatifs; Réservé UdeM; Urbanisme; Villes intelligentes

Playing with the Rules of the Game: Social Innovation for Urban Transformation - Thompson, Matthew (International Journal of Urban and Regional Research, 2019)
Innovation is perhaps the buzzword in local economic development policy. Associated narrowly with neoliberal ideas, conventional notions of innovation—like its capitalocentric counterparts, enterprise and entrepreneurialism—may promise higher productivity, global competitiveness and technological progress but do not fundamentally change the ‘rules of the game’. In contrast, an emerging field reimagines social innovation as disruptive change in social relations and institutional configurations. This article explores the conceptual and political differences within this pre‐paradigmatic field, and argues for a more transformative understanding of social innovation. Building on the work of David Graeber, I mobilize the novel constructs of ‘play’ and ‘games’ to advance our understanding of the contradictory process of institutionalizing social innovation for urban transformation. This is illustrated through a case study of Liverpool, where diverse approaches to innovation are employed in attempts to resolve longstanding socio‐economic problems. Dominant market‐ and state‐led economic development policies—likened to a ‘regeneration game’—are contrasted with more experimental, creative, democratic and potentially more effective forms of social innovation, seeking urban change through playing with the rules of the game. I conclude by considering how the play–game dialectic illuminates and reframes the way transformative social innovation might be cultivated by urban policy, the contradictions this entails, and possible ways forward.
Num Pages: 1168-1192 Place: Oxford, United Kingdom Publisher: Blackwell Publishing Ltd. Section: Articles
Keywords: Europe; Réservé UdeM; UK

Inclusion in social innovation through the primary and secondary use of technology: a conceptual framework - Oomens, I. M. F.; Scholten, C. (International Review of Applied Economics, 2020)
People with disabilities are an important actor and target group in social innovation initiatives worldwide, as there is a clear need for better inclusion of this group in society. A way to improve the inclusion of people with disabilities is the development of assistive technology. In practice, people with disabilities often use technologies of which the primary use is not that of an assistive technology. They use the technology for a different use and context than the developer intended – termed 'secondary use'. The current paper studies the factors that are needed to make the secondary use of technology a success. First, a literature review and explorative study in the Netherlands are performed, after which a framework on the secondary use of technology for inclusion, specifically for people with disabilities, is developed.
Keywords: EDI; Europe; Personnes en situation de handicap; Réservé UdeM

Research with a Solidarity Clinic: Design Implications for CSCW Healthcare Service Design - Vlachokyriakos, Vasilis; Crivellaro, Clara; Kouki, Hara; Giovanopoulos, Christos; Olivier, Patrick (Computer Supported Cooperative Work-the Journal of Collaborative Computing and Work Practices)
This paper reports on a long-term collaboration with a self-organised social clinic, within solidarity movements in Greece. The collaboration focused on the co-creation of an oral history group within the social clinic, aiming to record and make sense of a collection of digital oral histories from its volunteers and volunteers-doctors. The process aimed to support reflection and shape the future of the clinic's ongoing social innovation and to transform institutional public health services. Positioning the work of solidarity movement as designing social innovation, the work contributes to CSCW and 'infrastructuring' in Participatory Design aspiring to support social activism and social transformation processes. More specifically, through our empirical insights on the process of infrastructuring an oral history group within a social movement; and related insights about their ongoing participatory health service provision-we provide implications for CSCW concerned with its role in institutional healthcare service transformation.
Place: Dordrecht Publisher: Springer WOS:000665666500001
Keywords: Computer Supported Cooperative Work (CSCW); Europe; Participatory Design; Réservé UdeM

The impact of corporate social responsibility on innovation in small and medium‐sized enterprises: The mediating role of debt terms and human capital - Santos‐Jaén, José Manuel; Madrid‐Guijarro, Antonia; García‐Pérez‐de‐Lema, Domingo (Corporate Social Responsibility & Environmental Management, 2021)
The aim of this paper is to study the influence of corporate social responsibility (CSR) over small and medium‐sized enterprise (SME) innovation and the effect of two mediating variables, debt terms and human capital. Based on a sample of 2825 Spanish SMEs and applying a structural equations modeling, the results demonstrate that the effect of CSR on innovation is mediated by debt terms and by good human resource practices. Part of the positive effect of CSR on innovation occurs through these two variables, which, alone, positively and significantly affect innovation in SMEs. Consequently, the positive effect of CSR practices on debt terms through a decrease in asymmetric information goes further, also having repercussions on innovation. Additionally, the suitable development of human resource practices based on strategies oriented toward CSR allow companies to carry out greater and more efficient innovative activities. This paper contributes to the CSR literature considering the human resource management and the debt access in the relationship between CSR and innovation. The findings reveal important implications for policy makers and managers. For the former, the results show that it would be interesting to carry out actions aimed at assisting SMEs, especially those with fewer resources available, to implement a suitable CSR strategy, supporting sustainable development in SMEs. And, for the latter, CSR‐oriented innovation has proven to be a valuable strategy for more efficient SMEs management because of the multiple competitive advantages it generates.
Keywords: Europe; Responsabilité sociétale des entreprises; Réservé UdeM

Social Innovation and University Intellectual Property: Insights from the UK and Mexico - McDonagh, L.; Bonadio, E.; Alba Betancourt, A. (European Intellectual Property Review, 2020)
University intellectual property policies, and the accompanying strategies for incubation of IP via licensing and spin outs, have not received much analysis from academic lawyers. Moreover, despite the success of universities in the UK at generating income from IP, not much is known about how transferable this success is when considered in the light of a rapidly growing middle-income developing economy such as Mexico’s. In this article we analyse critically some of the key tenets of IP policies at universities in the UK to identify what the key legal principles underpinning university innovation are. We further consider the potential application of these principles in Mexico, where so far only a limited number of universities have developed IP policies and strategies in line with the incubator model. We explain how universities in Mexico could implement these research findings in their own IP policies. We further note that the mere provision of an IP policy is not a panacea – on its own it is insufficient for ensuring technology transfer and it may even encourage unnecessary patenting. Further investment in infrastructure and in establishing a culture of incubation and entrepreneurship is also required.
Publisher: Sweet and Maxwell
Keywords: Amérique latine; Europe; Libre accès; Propriété intellectuelle; UK

Vers un « modèle français » de régulation de l’intelligence artificielle fondé sur l’innovation sociale ? - Chevret-Castellani, Christine; Labelle, Sarah (Communication, technologies et développement, 2021)
Nous présentons dans cet article les résultats d’une enquête sur les politiques publiques de régulation de l’intelligence artificielle et en particulier sur les stratégies mises en œuvre dans des cadres socio-politiques aux échelles nationales, européennes et internationales. La France a créé des instances dans lesquels des « frottements » entre acteurs différents sont possibles, comme les groupes d’experts ou le Partenariat Mondial sur l’Intelligence Artificielle. Nous considérons que le travail de la part de l’ensemble des groupes sociaux, impliqués dans les instances que nous observons, est consubstantiel à la régulation. Les acteurs publics et privés s’organisent pour échanger et interagir de façon structurée, notamment par la mise en place de ces instances, comme le PMIA. Les dispositifs et instruments, auxquels les différents acteurs participent, contribuent à conférer un sens aux activités de régulation. Notre hypothèse repose sur l’émergence d’un « modèle français » de la régulation qui tend à promouvoir la « confiance » et dont le sens est de parvenir à l’acceptabilité sociale de l’IA.
Number: 10 Publisher: La Chaire Pratiques émergentes en technologies et communication pour le développement
Keywords: Europe; France; Intelligence artificielle; Internet; Modèle de réglementation; Politiques publiques; Réservé UdeM

Blockchain et Intelligence Collective pour le Design des Connaissances de l'Internet des Objets: Modélisation du pouvoir d'agir des objets connectés - Szoniecky, Samuel (Proceedings of the 1st International Conference on Digital Tools & Uses Congress, 2018)
Cet article est une réponse prospective aux besoins de l'Internet des Objets en termes de simplicité d'utilisation, de gestion de la sécurité et de préservation de la vie privée. Nous proposons de satisfaire ces besoins à travers une plateforme d'intelligence collective utilisant des cartographies sémantiques en réalité augmentées pour récolter les interactions des utilisateurs avec des objets connectés. L'association de l'intelligence collective et des cartographies sémantiques permet d'envisager un design de connaissances où les capacités d'action des objets connectés sont facilement compréhensibles et modifiables par les utilisateurs. Dans ce dispositif, les technologies de blockchain sont utilisées pour partager en sécurité l'expression des utilisateurs et ainsi augmenter la confiance dans l'Internet des Objets et par la même contribuer au développement d'une réflexivité collective sur les usages de ces écosystèmes sociotechniques.
Keywords: Europe; France; Internet des objets; Mesure de la perception; Réservé UdeM

Consommation et innovation sociale inversée dans l’espace francophone : quand les consommateurs participent à l’amélioration des conditions de vie des producteurs - Ledjou, Jean-Michel; Randrianasolo-Rakotobe, Hanitra (Revue Organisations & territoires, 2021)
L’Union européenne comme les pouvoirs publics français peinent à trouver des solutions aux crises agricoles. Le secteur laitier n’échappe pas à la règle. En 2016, quelque 7000 consommateurs français ont activement participé à la coconstruction d’une filière laitière guidée par un objectif social : améliorer les conditions de vie des producteurs. L’innovation repose ainsi sur une nouvelle méthode de fixation du prix de vente du lait conditionné. Nous montrerons par cet exemple ainsi que par d’autres exemples en France que ce type de coconstruction constitue une innovation sociale inversée. Cette dernière tire parti d’un demi-siècle d’apprentissage fondé sur l’institutionnalisation du « caractère équitable » d’un bien, lequel est au coeur du commerce équitable Nord-Sud. Le label « équitable » n’est donc plus réservé aux seuls pays en développement. Nous analyserons également la portée des technologies numériques (TN) qui réduisent la « distance sociale » entre producteurs, implantés au Sud ou au Nord, et consommateurs. Ainsi, les consommateurs peuvent arbitrer à travers les TN, et ce, dans plusieurs filières.
Number: 1
Keywords: Commerce équitable; Europe; Libre accès

From Research to Numbers: Role of Universities in Social Innovation - Cunha, Jorge; Ferreira, Carla; Araújo, Madalena; Benneworth, Paul (Innovations in Industrial Engineering, 2022)
Commonly, social innovation is defined as new ideas proposals to the needs of humans. However, there is a lack of a well-definition comprehensive leading the fragmentation of field research. On the other hand, the contribution of universities for social innovation development is still less investigated. In this sense, this study intends to explore interrelations between universities and social innovation in relation to different lines of investigation employed. For this, a content analysis was applied to results obtained by Cunha et al. [1]. Five categories of analysis were defined. Findings revealed that there are a number of studies that applied qualitative research to investigate practical examples of social innovation inside of universities and few empirical studies. A link among keywords social innovation, higher education, and social entrepreneurship was found. Furthermore, the analysis showed that there is not a leader country but a distribution across several countries, where Spain and United Kingdom stand out. Thus, this result suggests that it would be helpful to develop an instrument to measure academics’ engagement with social innovation research and practice. In addition, this research contributes to current knowledge regarding the role of universities in social innovation model, providing new theoretical and practical insights of investigation.
N'AVONS PAS ACCÈS
Keywords: Europe; Rôle des universités

The social impact of universities: assessing the effects of the three university missions on social engagement - Carl, Johannes; Menter, Matthias (Studies in Higher Education, 2021)
Whereas the economic impact of universities is undisputed, the social impact of universities remains vague. The purpose of this paper is to examine whether and how universities influence firms’ social engagement. Based on survey data of more than 7,000 German firms, our results reveal that universities positively affect firms’ social engagement mainly through teaching activities. Hence, our findings give impetus to a reinforcement of the university mission ‘teaching’ as a central lever for social change and increased social awareness as well as to a reorientation of the third university mission toward social needs. This paper thereby contributes to our understanding of the changing missions and values of universities and adds to the literature by exploring the underlying mechanisms of the social impact of universities. We conclude the paper with fruitful future avenues of research.
Keywords: Europe; Réservé UdeM; Rôle des universités

Social Innovation at Technical Universities – State of the Art - Berg, Julia; Leicht-Scholten, Carmen (Proceedings of ISPIM Conferences, 2021)
This paper presents the state of the art in promoting social innovation at five leading technical universities in Europe. We assess how these leading technical universities implement social innovation in their strategies, teaching, and research. The results show that all universities highlight the importance of finding solutions to global challenges and addressing Responsible Research and Innovation (RRI) as a fundamental university strategy for example by promoting social innovation. Moreover, all address the universities’ need to contribute to sustainability and the Sustainable Development Goals. However, social innovation does not play an important role in research and teaching as the results show that social innovation has so far been little addressed in research and teaching. Based on the political framework in the five European countries, we draw up conclusions for technical universities
N'AVONS PAS ACCÈS
Keywords: Europe; Rôle des universités

Contribution of Higher Education Institutions to Social Innovation: Practices in Two Southern European Universities - Monteiro, Sílvia; Isusi-Fagoaga, Rosa; Almeida, Leandro; García-Aracil, Adela (Sustainability, 2021)
The interactions between the higher education sector and society and industry have been attracting increased attention in terms of ways to develop social innovation solutions to societal problems. Despite calls from politicians and the existence of some guidelines, we know little about how higher education could incorporate social innovation activities into its structure and missions. This study examines some practice experiences in two southern European public universities in Portugal and Spain. We show that the third mission of universities, which includes social innovation, is both linked to the first two missions of teaching and research, depending on the university’s historical and social context. The high dependence of higher education institutions on economic returns increases the importance of political action to drive the development of social innovation activities. This conditioning factor seems to be intrinsic to some of the barriers that have been identified, such as lack of legitimization and recognition of social innovation practices at the formal governmental level.
Number: 7 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: Europe; Libre accès; Rôle des universités

University Medialabs: New Learning Spaces for Educational Innovation - Almaraz-Menéndez, Fernando; Martín-García, Teresa; López-Esteban, Carmen (Journal of Strategic Innovation and Sustainability, 2021)
Higher Education Institutions, like many other organizations, are facing pressure from the development of digital technologies as a push towards the digitization of their activities and towards a type of change that some describe as disruptive and that forces them to review their processes and structures. This article describes the case of the medialab of the University of Salamanca, MEDIALAB USAL, as an experience of new learning space in higher education. Its origin is explained from the experiences of citizen technology laboratories and experimental laboratories at the point of intersection between Art, Science and Technology. Its structure and working methods are explained, and its activities are illustrated through the description of four educational innovation projects based on different digital technologies: a mathematics didactics project using AppInventor, Wikipedia as a tool for knowledge generation, Arduino for innovation in the teaching of Fine Arts and a university Hackathon as an activity to introduce students to social and entrepreneurial innovation processes.
Number: 4
Keywords: Collaboration; Durabilité; Europe; Hackathon; Innovation pédagogique; Innovation sociale; Laboratoire vivant; Libre accès; Living Labs; Médialab; Technologies; numérique

Why are social enterprises good candidates for social innovation? Looking for personal and institutional drivers of innovation - Tortia, Ermanno C.; Degavre, Florence; Poledrini, Simone (Annals of Public and Cooperative Economics, 2020)
The last few years witnessed theoretical and practical contributions to the field of social innovation and social enterprise. However, analysis of the interplay between these two different realms is still limited. This article aims to fill some gaps in this respect. We deal with historical reconstruction of the concept of Social Enterprise and Social Innovation, and their conceptual premises. We consider the process of creation of social innovation in social enterprises. As members’ motivations, ownership rights and governance rules in social enterprises create a new relational context and new routines, which are germane to the production of social knowledge and deliberation, social innovation can be considered one of the main outcomes of this setting. Social motivations, collective action of a cooperative kind, multistakeholder governance and socialization of resources, and their interplay are singled out as main drivers of innovation. Social innovation is seen as akin to novelty in social interaction, a non-standardized and non-standardizable outcome of the operation of this organizational form.
Keywords: Entreprise; Europe; Innovation sociale; Mise en valeur; Réservé UdeM

The role of social innovation in criminal justice reform and the risk posed by proposed reforms in England and Wales - Fox, Chris; Grimm, Robert (Criminology & Criminal Justice: An International Journal, 2015)
The UK government has called for a rehabilitation revolution in England and Wales and put its faith in market testing. It hopes this will lead to greater innovation, resulting in reductions in re-offending while also driving down costs. However, many of the most innovative developments in criminal justice over recent decades have come through social innovation. Examples include restorative justice and justice reinvestment. In this article we argue that while social innovation will respond to some extent to conventional economic policy levers such as market testing, de-regulation and the intelligent use of public sector purchasing power it is not simply an extension of the neo-liberal model into the social realm. Social innovation, based on solidarity and reciprocity, is an alternative to the logic of the neo-liberal paradigm. In policy terms, the promotion of social innovation will need to take account of the interplay between government policy, social and cultural norms and individual and social capacity. Current proposals for reforming the criminal justice system may not leave sufficient scope to develop the conditions for effective social innovation.
Keywords: Europe; Réservé UdeM

Our impact - Schwab Foundation for Social Entrepreneurship (Schwab Foundation for Social Entrepreneurship)
The Schwab Foundation for Social Entrepreneurship launched its 2020 Impact Report which showcases the collective impact of the Schwab Foundation social entrepreneur community.
Keywords: Europe; Mesure d'impact; OBNL

Ashoka
Ashoka a été lancée en France en 2006. Depuis, 75 entrepreneurs sociaux ont été sélectionnés et bénéficient d’un accompagnement personnalisé par une équipe constituée d’une vingtaine de personnes, près de 80 mentors issus de l’Ashoka Support Network ainsi qu’une vingtaine de partenaires en mécénat de compétences. Le siège d’Ashoka France est situé à Station F, au coeur de l’écosystème entrepreneurial. Ashoka France a également contribué au développement de 2 structures : Share it et la Maison de l'apprendre.
Carte d'information Type d’organisme : Organisation non-gouvernementale / Réseau d'acteurs de changement en faveur de l'innovation sociale Échelle géographique : France et monde Type de contenu et outils proposés - Accompagnement des entrepreneurs sociaux - Connecter les acteurs de différents horizons (société civile, secteurs publics ou privés) - Actualités (nouvelles et tribunes) - Réseau et partenariat Public visé : Entrepreneur sociaux
Keywords: Europe; Organisme de soutien

Framing improvements of public innovation in a living lab context: Processual learning, restrained space and democratic engagement - Fuglsang, Lars; Hansen, Anne Vorre (Research Policy, 2022)
Public innovation has received increasing attention in recent years. Experiments with new governance structures, such as New Public Management and New Public Governance, have challenged the traditional top-down, internally driven forms of innovation in the public sector and have entailed a search for new forms of open, collaborative and interactive innovation, implying a reframing of public innovation activities. However, introducing these new frames of innovation causes uncertainties in the public sector, necessitating better understanding of how public innovation can be changed to address societal needs. This paper uses materials from case studies of 21 public living labs across Europe to analyse the lessons that can be learned from public sector participation in living labs in terms of their contribution to reframing public innovation. The “frame” construct is used to analyse and provide an understanding of how participation in living labs helps public actors to reframe innovation and address public and societal needs. Three living lab framings for changing public innovation are identified (processual learning, restrained space and democratic engagement), and the degree of intensity of these framings with respect to involving stakeholders and addressing societal challenges is discussed. The paper contributes to knowledge of public sector innovation by extending previous accounts of how public innovation can be improved.
Keywords: Europe; Innovation publique; Laboratoire vivant; Libre accès; Living Labs

innovation sociale - IATE European Union Terminology (IATE European Union Terminology, 2009)
conception et mise en œuvre de réponses créatives aux besoins sociaux
IATE - Entry ID 3501971
Keywords: Bases de données terminologiques; Europe; Libre accès